Effects of climate change on the surface waters of the Santa River, La Rinconada - Ancash – Peru - Pérez Campomanes, Giovene (2021)
The effect of climate change on the surface waters of the Santa River, the town center la Rinconada, Ancash, Peru, was assessed. Climate change was modeled between 2006 - 2015, through temperature, precipitation, and historical evapotranspiration versus surface waters based on water availability, and the best regression equations were selected. A validated survey of users of the Rinconada Irrigation Commission (CRR) was also taken. The best equation was exponential type for surface water and average precipitation. In contrast, for surface water and climate change the most appropriate was multiple linear regression. In relation to the survey, 83.33% strongly agree that they are concerned about climate change, and 81.37% agree that they are fully prepared for climate change caused by high temperatures. 27.5 % strongly disagree that the amount of water available in the canals has decreased because of climate change. It is concluded that it is possible to predict water availability in the face of the presence of climate change by applying regression users equations, and that there is concern of CRR users, in the face of the presence of climate change.